Comparison of negative pressure wound therapy with moist wound therapy in the treatment of diabetic foot ulcers with non-revascularisable peripheral vascular disease - Pallela, Someshwara Rao Narayana; Narahari, Padmavathi (International Surgery Journal, 2017)
Background: Diabetic foot problems are the commonest reason for hospitalization of diabetic patients (about 30% of admissions) and absorb some 20% of the total health-care costs of the disease more than all other diabetic complication. The numbers of patients with chronic wounds and wound complications continues to increase. Wound management is a challenge in diabetic wound. Chronic wounds require significant medical, nursing and financial input with poor long-term results. One-third of all diabetic patients have significant peripheral neuropathy and/or peripheral vascular disease (PVD). In India prevalence of foot ulcers in diabetic patients in clinic population is 3%. Over the past several years negative pressure wound therapy (NPWT) using vacuum- assisted closure has emerged as the treatment of complex wounds of the diabetic foot. Many reports on the use of Vacuum Assisted Closure (VAC) therapy after failed revascularization have found increased chances of success. Clinicians should consider negative pressure wound therapy as an adjunct to other modalities in an effort to avoid complications. Methods: Total of 51 patients were included in this prospective study. They were randomly divided into two groups, negative pressure wound therapy (NPWT) group (25 patients) and control group (26 patients) who were treated with regular dressings. All the patients included had peripheral vascular disease which was declared non-revascularisable after vascular workup. Initial mean surface area was measured in each patient. Transcutaneous oxygen pressure was recorded in all the patients and each patient followed up based on their granulation tissue development and need for amputation in each group. Results: After wound management, mean surface area of the diabetic wounds was 39.08cm2 in the NPWT group (P=0.019), and 38.63cm2 in the control group (P=0.327). The use of NPWT may be an effective initial wound therapy to achieve faster wound bed granulation showing signs of healing in 19 among 25 patients (76%) compared to control group 7 showed granulation among 26 patients (26%) (P=0.001). The incidence of secondary higher amputation in NPWT group is 6/25 (24%), the control group 17/26 (65%) (P=0.003), suggesting reduced incidence of secondary higher amputations in NPWT group. After treatment, the experimental group significantly improved in measures of foot ulcer surface area compared with the control group. Further studies are needed to clarify the effects and indications and to modify the technique of this alternative treatment for use on non healing wounds. Conclusions: NPWT-treated patients reached a successful wound treatment endpoint more rapidly, and the benefit was apparent in all wound sizes. NPWT appears to be a safer and efficacious method, than moist wound therapy for the treatment of diabetic foot ulcers.